The work is devoted to the study of the main aspects of technological education in the field of "technology". The concepts of continuous development of lifelong education, as well as the development of the system of continuing education, which is one of t - Ismatullaeva Holida Zukrullaevna; Yakubova Hilola Sunnatovna; Daminova Rano Baacitovna (Scholar Express Journal, 2022)
The work is devoted to the study of the main aspects of technological education in the field of "technology". The concepts of continuous development of lifelong education, as well as the development of the system of continuing education, which is one of the most important areas
Keywords: Continuous Technological Education; Professional Self-Education; Design; Priority